Calamagrostis nandadeviensis (Poaceae, Agrostidinae), a new grass species from India - Prasad, Dileshwar; Tripathi, Shailja; Jaiswal, Shubham; Yadav, Rekha; Agnihotri, Priyanka (Phytotaxa, 2021)
Calamagrostis nandadeviensis, a new species of Calamagrostis (Poaceae: Agrostidinae) from India (Valley of Flowers National Park of Uttarakhand and Rohtang Pass of Himachal Pradesh) is described and illustrated. C. nandadeviensis is morphologically allied to C. lahulensis and C. scabrescens but differs from them in having deeply bifid palea and fused lodicules. Data on distribution, habitat, biotic association are presented along with an illustration and comparative photo plate.